Molecular epidemiology and carbapenem resistance mechanisms of Pseudomonas aeruginosa isolated from a hospital in Fujian, China - Xie, Xueqin; Liu, Zhou; Huang, Jingyan; Wang, Xueting; Tian, Yuting; Xu, Pinying; Zheng, Gangsen (Frontiers in Microbiology, 2024)
The worldwide spread of Pseudomonas aeruginosa, especially carbapenem-resistant P. aeruginosa (CRPA), poses a serious threat to global public health. In this research, we collected and studied the clinical prevalence, molecular epidemiology, and resistance mechanisms of CRPA in Fujian, China. Among 167 non-duplicated P. aeruginosa isolates collected during 2019-2021, strains from respiratory specimens and wound secretions of older males in the intensive care unit dominated. Ninety-eight isolates (58.7 %) were resistant to at least one tested antibiotic, among which 70 strains were carbapenem-resistant. Moleclar typing of the CRPA isolates revealed they were highly divergent, belonging to 46 different sequence types. It is noteworthy that two previously reported high risk clones, ST1971 specific to China and the globally prevalent ST357, were found. Several carbapenem resistance-related characteristics were also explored in 70 CRPA isolates.Firstly, carbapenemase was phenotypically positive in 22.9 % of CRPA, genetically predominant by metallo-β-lactamase (MBL) and co-carrige of different carbapenemase genes. Then, mutations of the carbapenem-specific porins oprD and opdP were commonly observed, with frequencies of 97.1 % and 100.0 %, respectively.Furthermore, the biofilm formation and relative transcription levels of 8 multidrug efflux pump genes were also found to be increased in 48.6 % and 72.9 % of CRPA isolates compared to the reference strain PAO1. These findings will help fill the data gaps in molecular characteristics of CRPA on the southeastern coast of China and emphasize the urgent need for data-based specific stewardship for antipseudomonal practices to prevent the dissemination of CRPA.